2020
DOI: 10.1515/eng-2020-0018
|View full text |Cite
|
Sign up to set email alerts
|

Long-term urban traffic monitoring based on wireless multi-sensor network

Abstract: AbstractIncreasing the number of vehicles on the road network and the growing popularity of sustainable development of urban areas have resulted in the need for implementing efficient and cost-effective traffic measurement methods. From the perspective of traffic management, up-to-date information about vehicle density and access to historical data are the key components of traffic variability analyses. Rapid technological development based on Intelligent Transport Systems (ITS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The results showed that the smallest average relative error between the estimated number of cars and the actual traffic was less than 10%. In [18], the authors performed a traffic variability and dynamics analysis using a multi-sensor Bluetooth network for traffic volume monitoring, concluding that the long-term research indicated only minor variation in the number of vehicle detections and relatively stable traffic volume.…”
Section: Related Workmentioning
confidence: 99%
“…The results showed that the smallest average relative error between the estimated number of cars and the actual traffic was less than 10%. In [18], the authors performed a traffic variability and dynamics analysis using a multi-sensor Bluetooth network for traffic volume monitoring, concluding that the long-term research indicated only minor variation in the number of vehicle detections and relatively stable traffic volume.…”
Section: Related Workmentioning
confidence: 99%
“…Thanks to its advanced, inbuilt algorithms, the OnDynamic system is an advanced, automated measuring environment. The system has proved a useful tool for monitoring traffic conditions and analysing traffic long-term variability [33].…”
Section: Measurement Systemmentioning
confidence: 99%
“…For this reason, it is necessary to permanently monitor over a long period of time vehicle traffic and analyze the recorded data [12][13][14]. This will allow for a more precise analysis and a more objective assessment of the phenomena taking place as well as the values of their parameters.…”
Section: Introductionmentioning
confidence: 99%